Supramolecular gel to metal organic framework transformation - Chakraborty, Amit; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: gel; MOF; Supramolecular

Multistimuli-responsive interconvertible low-molecular weight metallohydrogels and the in situ entrapment of CdS quantum dots therein - Bera, Saibal; Chakraborty, Amit; Karak, Suvendu; Halder, Arjun; Chatterjee, Soumyajyoti; Saha, Subhadeep; Banerjee, Rahul (Chemistry of Materials, 2018)
Two low molecular weight metallohydrogels (ZALA and CALA) have been synthesized from an amino-acid based ligand precursor (LA) and two different metal salts [zinc acetate dihydrate (ZA) and cadmium acetate dihydrate (CA), respectively. These two hydrogels show a unique chemically stimulated interconversion to each other via a reversible gel-sol gel pathway. This programmable gel-sol reversible system satisfies logic operations of a basic Boolean logic (INHIBIT) gate. Also, these hydrogels can be degraded into different MOF phases at room temperature spontaneously or in the presence of chloride and bromide salts (NaCl and NaBr.). CdS quantum dots can be grown inside the CALA gel matrix (CdS@CALA) in the presence of small amount of Na2S. This CdS doped gel exhibits time dependent tunable emission (white to yellow to orange) as a consequence of a slow agglomeration process of the entrapped quantum dots inside the gel matrix. This luminescence property also reflects the corresponding gel derived MOFs (obtained either by self-degradation of CdS@CALA or via anion induction) as well. This, to the best of our knowledge, is probably the simplest way to make a CdS quantum dot based composite material where CdS is entrapped within the gel and the gel-derived MOF matrix.

Ultrastable imine-based covalent organic frameworks for sulfuric acid recovery: an effect of interlayer hydrogen bonding - Halder, Arjun; Karak, Suvendu; Addicoat, Matthew; Bera, Saibal; Chakraborty, Amit; Kunjattu, Shebeeb H.; Pachfule, Pradip; Heine, Thomas; Banerjee, Rahul (Angewandte Chemie-International Edition, 2018)
A rapid and scalable synthesis of six new imine-linked highly porous and crystalline COFs is presented that feature exceptionally high chemical stability in harsh environments including conc. H2SO4 (18M), conc. HCl (12M), and NaOH (9M). This is because of the presence of strong interlayer C-H center dot center dot center dot N hydrogen bonding among the individual layers, which provides significant steric hindrance and a hydrophobic environment around the imine (-C=N-) bonds, thus preventing their hydrolysis in such an abrasive environment. These COFs were further converted into porous, crystalline, self-standing, and crack-free COF membranes (COFMs) with extremely high chemical stability for their potential applications for sulfuric acid recovery. The as-synthesized COFMs exhibit unprecedented permeance for acetonitrile (280 Lm(-2) h(-1) bar(-1)) and acetone (260 Lm(-2) h(-1) bar(-1)).